2011
DOI: 10.1097/mej.0b013e328345d6fd
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the SALT and Smart triage systems using a virtual reality simulator with paramedic students

Abstract: The virtual reality platform seems to be a viable research tool for examining mass casualty triage. A small sample of trained paramedic students using the virtual reality system was able to triage simulated patients faster and with greater accuracy with 'Smart' triage than with 'SALT' triage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 23 publications
3
78
0
1
Order By: Relevance
“…VR in medical education ranges from dedicated simulation programs through to virtual environments in Second Life (Conradi et al, 2009). A comparative study by Cone, Serra, and Kurland (2011) indicated the efficacy of VR as a platform for paramedic student education. The main challenges of VR in medical education are the development costs and user familiarity with the VR-based applications (Conradi et al, 2009;Hsu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…VR in medical education ranges from dedicated simulation programs through to virtual environments in Second Life (Conradi et al, 2009). A comparative study by Cone, Serra, and Kurland (2011) indicated the efficacy of VR as a platform for paramedic student education. The main challenges of VR in medical education are the development costs and user familiarity with the VR-based applications (Conradi et al, 2009;Hsu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The participants’ task was to prioritize the 15 casualties according to the ABCDE algorithm and take into account the postulated circumstances. A colour-coded algorithm, red for priority 1 ( n  = 3), yellow for priority 2 ( n  = 3), green for priority 3 ( n  = 7) and black for dead ( n  = 2) was used, in accordance to the ABCDE and SALT triage algorithms [20, 26, 27]. A maximum of 15 points could be obtained, one point per correctly triaged patient.…”
Section: Methodsmentioning
confidence: 99%
“…Quality improvement in this field has consequently been limited to after-event reviews, simulations, mock drills, and the tinkering of experts. [6][7][8][9][10][11][12] While such methods of assessing mass casualty triage are doubtless better than nothing, they lack a compelling, large-scale evidence basis. Initial, primary triage of mass casualty incident victims is based on acuity and likelihood of survival.…”
Section: Introductionmentioning
confidence: 99%